Morphological Variation of Leaf Pattern of the Nepalese Taraxacum Spp. (Asteraceae) - Luintel, Sanjeev; Gyawali, Sabina; Paudel, Babu Ram; Shrestha, Mani; Shakya, Lokesh Ratna (Himalayan Biodiversity, 2017)
Morphological variation of leaf pattern is very common in flowering plants to non-flowering plants that were used to differentiate the species in genus to species level. In this study, we used leaf morphology as the key characters to separate the species of Nepalese Taraxacum. Samples were collected from different parts of Nepal and herbarium specimen were observed to find the variation between the different species of Taraxacum. Our study shows that the presence of two distinct group in this genus Taraxacum. Taxa one is characterized by leaf with double margin (e.g. Taraxacum eriopodum along with 3 other species) and another group is characterized by leaf with single margin (e.g. Taraxacum tibetanum along with 5 other species).